STUDI KEANEKARAGAMAN JENIS TUMBUHAN LIANA SEBAGAI SUMBER PAKAN PRIMATA DI STASIUN PENELITIAN CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG - Riduwan, .; Prayogo, Hari; Sisillia, Lolyta (JURNAL HUTAN LESTARI, 2019)
Liana is a species of plant that has a way of growing by creeping, spreading, or hanging on its host, but its roots are still attached to the ground. Liana is one of the primate feeds in Cabang Panti Research Station. The riset was conducted from August 15 - September 15 2018 at the Cabang Panti Research Station-Gunung Palung National Park. This riset aims to obtain data on the diversity of liana species and is expected to provide data and information about the diversity of these plant species. The results showed in five habitat types namely the peat swamp forest habitat - freshwater swamps found 79 individuals, alluvial soil found 54 individuals, sandy rocks found 59 individuals, Lowland granite found 56 individuals and highland granite found 38 individuals. The total number of the five habitat types is 286 individuals from 21 genus/species. Keywords: Cabang Panti Research Station, Diversity, Lianas Plants.